Nanotechnology for agricultural transformation: A review - Katel, Shambhu; Upadhyay, Koshraj; Mandal, Honey Raj; Yadav, Shubh Pravat Singh; Kharel, Ayush; Rijan, Rijan (Fundamental and Applied Agriculture, 2021)
Agribusiness has been confronted with a wide array of complications encompassing; stagnant crop yields, climatic variation, water inaccessibility, agrochemicals buildup, less supplement use proficiency, reduced soil organic matter which has subsequently influenced the worldwide food demand. For the eradication of those aforesaid concerns, there is a prerequisite of a pioneer innovation, such as ‘Nanotechnology’ to be incorporated in the plant breeding sector, which can alleviate those snags alongside securing environmental parameters. Basically, Nanotechnology is a new breakthrough that operates at the subatomic level, particle by iota for fabricating a structure, apparatuses, or gadgets forced with a new sub-atomic collection that can sustain and improve the current status of plant breeding. The application of nanotechnology in plant breeding comprehends; disease and vermin control, seed technology, plant genetic modification, monitoring of plant growth stages, incitement of hormonal impacts, and precise farming. Other than this wide relevance of nanotechnology, a few investigations show that nanotechnology imparts phytotoxicity effects, which can be a restrictive risk for the environment, beings, and natural boundaries. However, if we can eliminate the potential risks and outcomes of this innovation, it could potentially reform the entire agricultural cosmos. Furthermore, this paper summarizes several nanotechnological approaches in plant breeding, recompensing specific consideration to its current utilization, and moreover, scans the opportunities, potential advantages, associative risks, deterrents, and conceivable prospective changes.